2022
DOI: 10.1093/cid/ciac762
|View full text |Cite
|
Sign up to set email alerts
|

Virologic Failure Following Low-level Viremia and Viral Blips During Antiretroviral Therapy: Results From a European Multicenter Cohort

Abstract: Background It is unclear whether low-level viremia (LLV), defined as repeatedly detectable viral load (VL) of <200 copies/mL, and/or transient viremic episodes (blips) during antiretroviral therapy (ART), predict future virologic failure. We investigated the association between LLV, blips, and virologic failure (VF) in a multi-center European cohort. Methods People with HIV-1 who started ART 2005 or later were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 27 publications
5
38
1
Order By: Relevance
“…8,9 Previous studies supporting the presence of active viral replication have reported that ART resistance mutations can accumulate when viremia persists in the low but detectable range 10,11 and that NSV can increase the risk of virologic failure. 12 While these factors can cause persistent NSV, other evidence has showed that persistent NSV can be maintained for long periods without leading to high-level virologic failure or the development of new resistance mutations. [13][14][15][16][17][18] While suboptimal ART adherence or emerging drug resistance may play a role in a subset of individuals with NSV, alternative mechanisms seem to underlie NSV in other PWH.…”
Section: Mainmentioning
confidence: 99%
“…8,9 Previous studies supporting the presence of active viral replication have reported that ART resistance mutations can accumulate when viremia persists in the low but detectable range 10,11 and that NSV can increase the risk of virologic failure. 12 While these factors can cause persistent NSV, other evidence has showed that persistent NSV can be maintained for long periods without leading to high-level virologic failure or the development of new resistance mutations. [13][14][15][16][17][18] While suboptimal ART adherence or emerging drug resistance may play a role in a subset of individuals with NSV, alternative mechanisms seem to underlie NSV in other PWH.…”
Section: Mainmentioning
confidence: 99%
“…Findings from recent studies 6 support the monitoring of parameters like viral load in the follow‐up of HIV‐positive patients since this enables the detection of the so‐called blips (transient viraemic episodes) and low‐level viremia that can appear during ART treatment and seem to be associated with increased risk of subsequent virologic failure.…”
mentioning
confidence: 90%
“…These can be classified as viral "blips," typically defined as transient detectable HIV viral loads that subsequently return below the lower limit of detection, or as persistent low-level viremia (pLLV) in which the viral load remains less than 200 cpm but presents as multiple consecutive (2 or more) detectable viral loads. 11 The frequency of viral blips and pLLV with oral ART varies significantly across studies, partly due to varying definitions and viral load cutoffs. Although the clinical impact of viral blips is less clear, pLLV has been associated with increased risk of virologic failure in several studies using orally administered ARV regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Although the clinical impact of viral blips is less clear, pLLV has been associated with increased risk of virologic failure in several studies using orally administered ARV regimens. [11][12][13] The mechanism of pLLV continues to be elucidated with studies showing an association with adherence to oral ART. 14 However, other proposed mechanisms include clonal expansion of infected T cells and inadequate drug penetration into sanctuary sites.…”
Section: Introductionmentioning
confidence: 99%